General guidelines for halal food preparation: unified standard of halal certification is important to globalize halal products - Jaswir, Irwandi (TM-Info-Media Sdn. Bhd., 2009)
Generally. all things created by God (Allah) are permitted, with a few exceptions thaf are prohibrted (haram) by clear and definite injunctions in the authentic sources according to Muslims: fhe Qur'an and Prophet Mohammad traditions (sunnah). In term of meat, these exceptions include pork, blood and meats of animals that died of causes other than proper slaughtering. The basic reasons for the prohibition of things are due to impurity and harmfulness. Basically, halal requirements are in accordance with the conventional quality standards (ISO, HAACP, Codex, GHP, GMP, etc). Therefore, halal products are typically also viable for non-Muslim consumers.